Contrasting Roles of IL-22 and IL-17 in Murine Genital Tract Infection by Neisseria gonorrhoeae - Russell, Michael W.; Feinen, Brandon (Frontiers in Immunology, 2012)
Murine genital tract infection with Neisseria gonorrhoeae has previously been found to induce IL-17 which is important in both recruitment of neutrophils and prompt clearance of the infection. As IL-22 is another Th17-related cytokine that has been implicated in the immune responses in several infection models, we investigated its role in vaginal gonococcal infection of mice. Production of IL-22 was observed in response to stimulation with N. gonorrhoeae in both mouse splenic mononuclear cells and vaginal tissue explants cultured ex vivo. Tissue from mice genetically deficient in IL-22 showed diminished production of IL-6 and the CXC chemokine KC in response to N. gonorrhoeae, whereas IL-17 and the chemokines LIX and MIP-2α were produced to the same extent as in wild-type tissue. IL-22-deficient mice were unexpectedly resistant to genital tract infection with N. gonorrhoeaein vivo, but showed no change in the influx of neutrophils to the site of infection. These results reveal divergent roles for IL-17 and IL-22 in response to gonococcal infection.